The application of phosphor Sr4La(PO4)3O:Ce3+,Tb3+,Mn2+ on white light-emitting diodes - My Hanh Nguyen Thi; Phan Xuan Le (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Using a high temperature solid-state technique, various phosphors Sr4La(PO4)3O:Ce3+, Tb3+,Mn2+ (SLPO:Ce,Tb,Mn) were produced. In Sr4La(PO4)3O, the luminescence characteristics, thermal stability, and energy conversion between Ce3+ and Tb3+-Mn2+ have been thoroughly studied. The sensitizer Ce3+ particles inclusion could considerably improve the feeble Tb3+ green radiation and Mn2+ red radiation via energy transfer. By adjusting the scale of Ce3+/Tb3+ over Ce3+/Mn2+ atoms, the color of the emission may be changed. White light was produced in the Sr4La(PO4)3O:0.12Ce3+,0.3Mn2+ specimen with chromatism coordinates of (0.3326, 0.3298), showing that the phosphors SLPO:Ce,Tb,Mn possess promising application on WLEDs. The conclusion is supported by Mie-scattering theory and Lambert-Beer's law.